A chromosome level genome assembly of Pseudoroegneria Libanotica reveals a key Kcs gene involves in the cuticular wax elongation for drought resistance - Xingguang Zhai; Dandan Wu; Chen Chen; Xunzhe Yang; Shaobo Cheng; Lina Sha; Shuhan Deng; Yiran Cheng; Xing Fan; Houyang Kang; Yi Wang; Dengcai Liu; et al. (BMC Genomics, 2024)
Abstract Background The genus Pseudoroegneria (Nevski) Löve (Triticeae, Poaceae), whose genome symbol was designed as “St”, accounts for more than 60% of perennial Triticeae species. The diploid species Psudoroegneria libanotica (2n = 14) contains the most ancient St genome, exhibited strong drought resistance, and was morphologically covered by cuticular wax on the aerial part. Therefore, the St-genome sequencing data could provide fundamental information for studies of genome evolution and reveal its mechanisms of cuticular wax and drought resistance. Results In this study, we reported the chromosome-level genome assembly for the St genome of Pse. libanotica, with a total size of 2.99 Gb. 46,369 protein-coding genes annotated and 71.62% was repeat sequences. Comparative analyses revealed that the genus Pseudoroegneria diverged during the middle and late Miocene. During this period, unique genes, gene family expansion, and contraction in Pse. libanotica were enriched in biotic and abiotic stresses, such as fatty acid biosynthesis which may greatly contribute to its drought adaption. Furthermore, we investigated genes associated with the cuticular wax formation and water deficit and found a new Kcs gene evm.TU.CTG175.54. It plays a critical role in the very long chain fatty acid (VLCFA) elongation from C18 to C26 in Pse. libanotica. The function needs more evidence to be verified. Conclusions We sequenced and assembled the St genome in Triticeae and discovered a new KCS gene that plays a role in wax extension to cope with drought. Our study lays a foundation for the genome diversification of Triticeae species and deciphers cuticular wax formation genes involved in drought resistance.